2007
DOI: 10.1017/s0033291706009688
|View full text |Cite
|
Sign up to set email alerts
|

Testing the self-medication hypothesis of depression and aggression in cannabis-dependent subjects

Abstract: Subjects with prior depression do not use cannabis as a mean of self-medication. They are more likely to experience specific increases of adverse symptoms while under the influence of cannabis, and are less likely to experience specific symptom relief. There is some evidence that cannabis is used as a means of self-medication for problems controlling aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 54 publications
11
62
0
1
Order By: Relevance
“…On the other hand, it should be considered that patients with primary depressive symptoms are at a higher risk of using cannabis (Feingold, Weiser, Rehm, & Lev-Ran, 2015), and could use cannabis to improve their mood (Arendt et al, 2007;Kandel & Chen, 2000;Kandel, Davies, Karus, & Yamaguchi, 1986;Miller-Johnson, Lochman, Coie, Terry, & Hyman, 1998). However, it has also been suggested that the direction of this relationship is inverse, in other words, cannabis use would increase the risk of depression and anxiety, with the decrease in motivation associated with use being a symptom of depression (Bovasso, 2001;Fergusson et al, 2002;Rey & Tennant, 2002).…”
Section: Cannabis Use Mood and Anxiety Disordersmentioning
confidence: 99%
“…On the other hand, it should be considered that patients with primary depressive symptoms are at a higher risk of using cannabis (Feingold, Weiser, Rehm, & Lev-Ran, 2015), and could use cannabis to improve their mood (Arendt et al, 2007;Kandel & Chen, 2000;Kandel, Davies, Karus, & Yamaguchi, 1986;Miller-Johnson, Lochman, Coie, Terry, & Hyman, 1998). However, it has also been suggested that the direction of this relationship is inverse, in other words, cannabis use would increase the risk of depression and anxiety, with the decrease in motivation associated with use being a symptom of depression (Bovasso, 2001;Fergusson et al, 2002;Rey & Tennant, 2002).…”
Section: Cannabis Use Mood and Anxiety Disordersmentioning
confidence: 99%
“…Additionally, the hypothesis that depressed individuals use Cannabis as a mean of self-medication proposed by preclinical studies [58] has not been fully supported by clinical data yet [59,60]. By contrast, some data support the hypothesis that Cannabis use precipitates depression [61][62][63][64][65], where genetic and environmental factors could play a pivotal role [66][67][68].…”
Section: Cannabis Endocannabinoid System and Depression: Clinical Anmentioning
confidence: 99%
“…Moreover, a further implication of these findings is that the goal of treatment should be abstinence for the illicit substances most predictive of IPV, rather than merely a reduction in the use of such substances. However, further research is needed to determine whether the most productive targets for intervention should be personality factors associated with drug use (e.g., anger and poor self-regulation; Arendt et al, 2007) or drug use itself. Overall, findings suggest that the role of alcohol problems in IPV perpetration may not be as strong as has previously been considered, because of the role of antisocial behavior and to polysubstance use.…”
Section: Limitations and Conclusionmentioning
confidence: 99%